Pelatihan Peningkatan Nilai Produk Holtikultura Berbasis Digitalisasi pada Kelompok Tani Langke Rembong - Tiwu, Maria Indriyani Hewe; Ballo, Fransina W.; Molidya, Aldarine; Tomosowa, Olivia L. E (Penerbit Goodwood, 2025)
Purpose: The aim of this training to develop the skills and expertise of horticultural farmer groups through digital marketing to increase farmer income. Methodology/approach: The method used is socialization and training for horticulture farmer groups, Langke Rembong, Central Manggarai Regency, East Nusa Tenggara Province. This training begins with the socialization of increasing the value of horticultural products and marketing strategies through online marketing. Training to increase the value of horticultural products is carried out on online packaging and marketing using social media. Results/findings: Socialization and training activities have provided knowledge transformation and direct application regarding increasing the value of horticultural farming products and online marketing in the form of Facebook business. and increasing sales of horticultural farming products and expanding market networks thereby providing economic improvements for farmer groups in Langke Rembong. Conclusions: This community service program successfully enhanced the value of horticultural products through digitalization and online marketing, while strengthening the farmers’ economy in Langke Rembong through continuous assistance. Limitations: This training has not yet reached the stage of distributing horticultural agricultural products to hotels and restaurants in the Labuan Bajo tourism area. Contribution: This training improving their skills to digital marketing and expanding their share market of holticultural products and improving their economics household.